Common Pitfalls in the Interpretation of COVID-19 Data and Statistics - Andreas Backhaus (Intereconomics)
Abstract Policymakers, experts and the general public heavily rely on the data that are being reported in the context of the coronavirus pandemic. Daily data releases on confirmed COVID-19 cases and deaths provide information on the course of the pandemic.